PWE-145 Contemporary uk experience with preoperative chemoradiotherapy and surgery for oesophageal cancer. (22nd June 2015) - Noble, F; Ponichtera, J; Sharland, D; Byrne, J; Kelly, J; Jackson, A; Bateman, A; Underwood, T
Abstract : Introduction: The optimal neoadjuvant therapy regime for cancers of the oesophagus and OGJ remains controversial. In the UK preoperative chemotherapy is the standard of care, and we have been slow to adopt chemoradiotherapy (CRT) fearing increased surgical morbidity and under-treatment of systemic disease. The CROSS trial has led to a renewed interest in the use of CRT in the UK. We present our recent experience of patients treated with CRT and surgery for oesophageal carcinoma. Method: All patients planned for CRT and surgery in a single UK institution were included. CRT consisted of carboplatin (AUC2) and paclitaxel (50 mg/m 2 ) weekly x 5 with concurrent radiotherapy (41.4Gray in 23 fractions, n = 25 (CROSS regime); 45Gray in 25 fractions, n = 4) for 29 patients and 2 patients had Oxaliplatin, Capecitabine (OxCap) and RT (45Gray in 25 fractions). In 5 CRT was preceded by 2 cycles of OxCap chemotherapy. Results: Radiotherapy 31 patients (median age 66 years; male 21 (68%): female 10 (22%)) with 13 adenocarcinomas (AC) and with 17 squamous cell carcinomas (SCC) underwent CRT. One patient (3%) died during CRT after oesophageal perforation at OGD. 3 patients (9.7%) were admitted to hospital (neutropenic sepsis 1; non-neutropenic sepsis 2). The median time between CRT and surgery was 10 weeks (range 5.7–14.1). 8 patients are awaiting resection. Surgery 22 patients have completed CRT and surgery. All patients underwent an oesophagectomy (minimally invasive: 15 (62.2%); Ivor Lewis: 7 (30.4%); Mckeown: 1 (4.3%)) with median length of stay: 10 days (range 6–45). There were no deaths. Complications according to Clavien-Dindo were Grade 1: 1 (4.5%); Grade 2: 10 (45.5%); Grade 3: 1 (4.5%); Grade 4: 1 (4.5%) with no complications in 9 (40.9%) patients. One (4.5%) patient had an anastomotic leak and this required reoperation and oesophageal exteriorisation with subsequent colonic interposition. 6 (27%) patients experienced a post-operative cardiac arrhythmia. There were 6 (27%) respiratory complications and no chyle leaks. Pathology 21 pathology reports were available with one under analysis. Complete pathological response (47.6%) was observed in 8 (72.7%) SCCs and 2 (20%) ACs (Tumour regression grade (TRG)1: 10 (47.6%); 2: 6 (28:6%); 3: 3 (14.3%); 4: 2 (9.5%); 5: 0). 20 (95.2%) patients had complete (R0) resection. Median nodal yield was 22 (range 8–65). Conclusion: In a single centre UK series, CRT and surgery for oesophageal cancer is safe and effective in the short term. This may in part be explained by increasing the time between the CRT and surgery from 6 to 10 weeks without compromising tumour pathology. Disclosure of interest: None Declared.